ZWIĄZKI BANKÓW Z FIRMAMI UBEZPIECZENIOWYMI I PERSPEKTYWY ICH ROZWOJU W POLSCE - Śliperski, Marek (Wydział Prawa i Administracji UAM, 1998)
Problems of theoretical and empirical character which focus on many aspects of a kind of activity called bancassurance have been touched in the article. Also an attempt was made to determine a set o f conditions for future development of such a kind of banks’ activity in Poland. In the first part o f the paper the Author has presented the very beginning of forming the idea of bancassurance in practice of banks and insurance firms against the backgroung of changes occuring on the world financial market. Notions such as cross-selling and standardisation of financial services have been discussed - in tight relation with connections between banks and insurances firms. Second part of the paper presents circumstances of such connections, an analysis of possible organisational forms as well as profits and risk resulting for a bank out of this activity. Particular attention has been drawn to a description of usefulness of banks’ network in purchasing insurances services; basic differences between a bank service and an insurance service were also defined. These differences become very often an object of considerations upon the elements (for example: degree of target integration, culturally based conflicts, risk tolerance) which must necessarily be taken into account for to operate successfully the activity called bancassurance. In the last part of the paper an evaluation of first examples of bancassurance in Poland was presented. In the measure where Polish national economy becomes more and more internationalised it seems to be justified to watch very carefully phenomenons happening on financial markets of highly developed Western countries. The Author puts forwards a thesis that in spite of many material obstacles the Polish commercial banks do have a real chance - i f only high rate of economic growth is maintained - to successfully realise some more closer connections with insurances firms and, this way, to share a success.
CONNECTIONS OF BANKS WITH INSURANCES FIRMS AND PERSPECTIVES FOR THEIR DEVELOPMENT IN POLAND